2013
DOI: 10.5491/shaw.2013.4.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Psychometric Properties of the Chinese Version of the Work-Related Quality of Life Scale-2 in the Nursing Profession

Abstract: ObjectivesAs quality of work-life (QWL) among nurses affects both patient care and institutional standards, assessment regarding QWL for the profession is important. Work-related Quality of Life Scale (WRQOLS) is a reliable QWL assessment tool for the nursing profession. To develop a Chinese version of the WRQOLS-2 and to examine its psychometric properties as an instrument to assess QWL for the nursing profession in China.MethodsForward and back translating procedures were used to develop the Chinese version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
3
13
0
1
Order By: Relevance
“…The results of our survey are consistent with other findings in the literature. The results of this study are consistent with findings reported earlier by Lin et al (2013aLin et al ( , 2013b and Gillet et al (2013).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of our survey are consistent with other findings in the literature. The results of this study are consistent with findings reported earlier by Lin et al (2013aLin et al ( , 2013b and Gillet et al (2013).…”
Section: Discussionsupporting
confidence: 83%
“…They also reported that a leisure benefit system was a coping resource for frontline employees' work-to-leisure conflict. Lin et al (2013b), in other work, studied psychometric properties of the Chinese version of the Work-Related Quality of Life Scale-2 in the nursing profession.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the format of the WRQoL-T is the same as the original WRQoL scale, that is, 23 questions that use a 5-point Likert scale, thus ensuring technical equivalence. The WRQoL-T is more appropriate for assessing the QWL of nurses in Taiwan than a similar scale that was recently translated into Chinese for use in China (Lin, Chaiear, Khiewyoo, Wu, & Johns, 2013). Although the latter scale is also in Chinese, it uses simplified Chinese characters rather than the traditional characters that are used in Taiwan, Hong Kong, and Macau.…”
Section: Discussionmentioning
confidence: 99%
“…A list of items was generated by adapting the items of existing generic scales (Casio, 1992;Walton, 1975;Timossi et al, 2008;Kanten and Sadullah, 2012;Lin et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, some scholars affirm that efforts for building universal conceptualization of QWL may be in vain and ineffective (Lin et al, 2013;Mirkamali and Thani, 2011). Furthermore, some arguments have been advanced to prove that QWL model is associated to organizational culture and work settings (Lin et al, 2013). Therefore, to be of pragmatic value, a QWL must be either by industry or setting specific.…”
Section: Introductionmentioning
confidence: 99%